Political factors and women's entrepreneurial performance - Arooj Zeb; Shahid Jan; Anjum Ihsan; Fayaz Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This paper investigates the existing political environment in Pakistan and its impact of women entrepreneurial performance. The importance of having a stable political environment for flourishing entrepreneurial activities has also been discussed. For this purpose, the study employs a research design where self-administered questionnaires were used to collect data from two groups of Pakistani women entrepreneurs; Registered and Non-Registered. The registered members were selected from the seven women chambers of commerce and industries of Pakistan using a stratified random sampling method whereas the non-registered members were selected from the groups on Facebook. The quantitative method of research has been employed using sample size of 506. Multiple regression analyses reveal that there is an impact of political factors on women entrepreneurial performance for both the groups. The results also show that women entrepreneurs believe that government is not supporting them for carrying out the activities for running their enterprises.
Keywords: 330; women entrepreneurs; political factors; entrepreneurial performance; registered entrepreneurs; non- registered entrepreneurs